Carotenoid Production by Rhodosporidium paludigenum Using Orange Peel Extract as Substrate - Warjoto, Renna Eliana; Jennifer, Jennifer; Lay, Bibiana Widyawati (Biosaintifika: Journal of Biology & Biology Education, 2020)
Carotenoids are fat-soluble pigments that have various benefits in health and beauty. The demand and market of carotenoids are increasing; thus, the faster and cheaper biological production of these pigments using microorganisms is desired. In this study, the optimum medium pH and nitrogen concentration for carotenoid production by Rhodosporidium (R.) paludigenum using orange peel extract as substrate were determined. The soluble sugars from orange peels were extracted using distilled water at 100 Â°C. The yeast inoculum was cultivated in Yeast Peptone Dextrose (YPD) media before fermentation. The independent variables in the fermentation factorial design included initial medium pH (5; 6; and 7) and nitrogen concentration (0; 1; and 1.75 g/L urea in the medium). The decrease in reducing sugar concentration and the increase in biomass dry weight during fermentation demonstrated carbon source consumption by R. paludigenum for growth and carotenoid production. On the sixth day of fermentation (D6), the culture was harvested for the total carotenoid extraction and determination. The highest total carotenoid yield (107.63 Âµg/g) was achieved by the treatment group with an initial medium pH of 6 without nitrogen supplementation. This result indicated the orange peel extract potential as a substrate for carotenoid production using R. paludigenum as a workhorse. This was the first reported research in natural carotenoid generation using R. paludigenum (strain InaCC Y-236) locally isolated in Indonesia as the producer and orange peel extract as the substrate. Thus, this research would enrich the microbial carotenoid exploration and waste valorization to value-added products at the same time. The study can then be developed further and upscaled for industrial applications.Â